ANALISIS PENERAPAN STRATEGI COST TRANSPARENCY PADA USAHA COFFEE ROASTERY - Haritz, Ahmad Nauval; Susilowati, Christin (Jurnal Kewirausahaan dan Inovasi, 2022)
Business competition in coffee industry is increasing in every year. Coffee consumption and production in Indonesia have been increasing drastically during the last five years. It has also been recorded that the number of coffee shops tripled only from 2016 to 2019. Therefore, coffee businesses need to apply different strategies in order to stay exist and competitive. This research was conducted at Langgan Coffee Roasters, a business that uses cost transparency whose main activities are roasting and selling coffee beans through subscription. The goal of this study is to identify how the strategy is applied and how their customers respond to it. The data of this research was harvested through interviews, observations, and documentations. This study finds that cost transparency is applied by opening the cost structure that constitutes the product to the public through Google Sheets. Their customers respond to it well since they can get better product knowledge and can make better budget planning before making transaction. Then, as they trust the company more, both parties have a closer relationship.